СOMPLIANCE IN THE TREATMENT OF ROSACEA AND PSYCHOEMOTIONAL STATES - Shakirova , A.; Chalikova , A.; Zamirbekova , K.; Kainazarova , K.; Islamova , G. (EurasianUnionScientists, 2020)
The paper presents the main psychological problems in patients with rosacea, their impact on adherence to therapy, and the results of their own observations of complex therapy. Acquisition of rapid positive results in therapy affected the patients’ compliance to the prescribed treatment.